Immunoglobulin-containing cells in the intestinal mucosa and immunoglobulins in the intestinal juice in children - Savilahti, E. (1972)
The numbers of immunoglobulin-containing cells in the mucosae of the small intestine and rectum were counted by a direct immunofluorescence technique in biopsy specimens from children. Immunoglobulins in the intestinal juice of the same patients were quantified by electroimmunodiffusion. In all biopsy specimens IgA-containing cells predominated. These cells were more numerous in the specimens from children over 2 years of age than in those of younger ones. The cells seemed to be fairly evenly distributed along the intestinal tract. The number of IgM-containing cells did not change with age in the group studied. In the intestinal juice the mean content of IgA was higher than that of the other immunoglobulins. More IgM and less IgA were found in the juice of infants under 2 years of age than in that of older children. The results suggest that quantitatively the IgA-producing system of the gut is not fully developed in infancy, whereas the reverse is true for the cells producing IgM.